The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s00277-007-0328-0
|View full text |Cite
|
Sign up to set email alerts
|

Primary follicular lymphoma of the cervix uteri: a review

Abstract: Primary non-Hodgkin's lymphoma of the cervix is a rare disease, of which a subgroup of follicular lymphoma constitutes only 8.5%. There is not an established treatment protocol neither for primary cervical lymphoma nor for its follicular subgroup. We presented a case with Ann Arbor stage IEA (Extra-nodal involvement and absence of weight loss, fever, night sweat) primary follicular lymphoma of the cervix. She was treated with chemotherapy followed by pelvic radiotherapy. Upon relapse with a nodal neck mass, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Rituximab was used in only five patients as the majority of patients were treated in the pre-monoclonal antibody era. [10][11][12] Both our patients received rituximab-CHOP and showed excellent responses with no evidence of disease at 20 and 19 months post-treatment. This suggests addition of immunotherapy in the form of rituximab is of value in improving response rates, as has been observed in other nodal lymphomas.…”
Section: Treatmentmentioning
confidence: 91%
See 2 more Smart Citations
“…Rituximab was used in only five patients as the majority of patients were treated in the pre-monoclonal antibody era. [10][11][12] Both our patients received rituximab-CHOP and showed excellent responses with no evidence of disease at 20 and 19 months post-treatment. This suggests addition of immunotherapy in the form of rituximab is of value in improving response rates, as has been observed in other nodal lymphomas.…”
Section: Treatmentmentioning
confidence: 91%
“…To preserve reproductive function in young patients, combination chemotherapy alone has been advocated in some case reports. 12,17 Survival Disease-free survival in this review ranged from 5 months to 8 years. Vang et al study of 10 patients reported a very good 5-year survival rate of 83%.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…HM of the GYN tract are considered as rare neoplasms; however, there are several cases described in the literature 3,4,6,9,12,13,17,[19][20][21][22][23][24][25][26][27] emphasizing the diagnostic difficulties these tumors pose for the clinician and the pathologist. Although primary HM of GYN is rare, secondary involvement of this anatomical site is reported to be present in 7-30% of women with disseminated disease, 1 or can be seen as a result of relapse of AML 28 or blastic transformation of CML.…”
Section: Discussionmentioning
confidence: 99%
“…Colposcopic findings in primary cervical lymphomas are unremarkable, or if present are rather nonspecific. Diffuse enlargement of the cervix, so-called barrel-shaped cervix or polypoid masses are reported in the literature, 1,4,11,12 whereas ulcerated cervical or vaginal lesions are rarely observed and they tend to be seen in patients with leukemic infiltrates. 13,14 In patients with primary uterine lymphomas, diffuse enlargement of the uterus is often noted, which can mimic fibroids radiologically.…”
mentioning
confidence: 99%